The Psychological and Social Impact of Covid-19: New Perspectives of Well-Being - Saladino, Valeria; Algeri, Davide; Auriemma, Vincenzo (Frontiers in Psychology, 2020)
The recent Covid-19 pandemic has had significant psychological and social effects on the population. Research has highlighted the impact on psychological well-being of the most exposed groups, including children, college students, and health workers, who are more likely to develop post-traumatic stress disorder, anxiety, depression, and other symptoms of distress. The social distance and the security measures have affected the relationship among people and their perception of empathy toward others. From this perspective, telepsychology and technological devices assume important roles to decrease the negative effects of the pandemic. These tools present benefits that could improve psychological treatment of patients online, such as the possibility to meet from home or from the workplace, saving money and time and maintaining the relationship between therapists and patients. The aim of this paper is to show empirical data from recent studies on the effect of the pandemic and reflect on possible interventions based on technological tools.